Ultrasound elastography techniques for the therapeutic monitoring of breast cancer - Di Battista, A (2011)
The composition, distribution and interaction of tissues found in tumours and their surrounding stroma has to date revealed a wealth of information about cancer biology. There exists a strong need to be able to measure these properties in vivo in order to provide further understanding and ultimately lead to better treatment for cancer patients. These interactions can manifest themselves in the form of distinctive biomechanical properties which ultrasound elastography, an image processing technique used to evaluate tissue stiffness, is particularly well suited to monitor. Much focus of elastography in breast cancer has been on diagnosis. However, it has always lacked the selectivity and sensitivity to be of reliable use in clinic. Moreover, with simple biopsies taken as the gold standard, the position of diagnostic tool has already been filled. The focus of this doctoral research has been to evaluate the role elastography can play in breast cancer after diagnosis, when therapy begins. Modifications and new applications of the technique were an essential part of this research. A new robust and efficient elastography algorithm was developed to meet the demands of freehand elastography imaging. In addition, a method for defining outlying data in strain images was produced which led to a technique for normalising and displaying images with a consistent colour mapping scheme. With the basic framework in place, the exploration into the non-linear properties of tissue was carried out using hybrid freehand imaging of viscoelasticity (HYFIVE) which took advantage of high ultrasound frame rates to measure tissue creep responses. The HYFIVE system was comprised of a novel probe canister device that was capable of acquiring < 2s worth of data to produce good measures of tissue viscosity. An experiment to show the ability of elastography to improve tumour sizing revealed a significant accuracy increase (∼20%) over conventional ultrasound B-mode. A final experiment exploited tumour/stroma behaviour to follow the response of neo-adjuvant breast cancer patients over multiple cycles of chemotherapy. Results from a pilot study suggest that elastography, in conjunction with standard B-mode, could be used as an early indicator to tumour response, with greater sensitivity over conventional ultrasound analysis. All of the results show that ultrasound elastography can significantly contribute to the understanding of breast cancers and provide viable clinical tools to put to practical use.